Genetic population structure of the precious coral Corallium japonicum in the Northwest Pacific - Kise, Hiroki; Iguchi, Akira; Saito, Naoki; Yoshioka, Yuki; Uda, Koji; Suzuki, Tomohiko; Nagano, Atsushi J.; Suzuki, Atsushi; Iwasaki, Nozomu (Frontiers in Marine Science, 2023)
Population sizes of the Japanese red coral Corallium japonicum have been severely affected by poaching and overfishing. Although genetic structure and connectivity patterns are considered important parameters for conservation strategies, there are few studies focusing on the population genetics of C. japonicum in the Northwest Pacific. We examined the genetic population structure of C. japonicum, in the Northwest Pacific. We used restriction-site-associated DNA sequencing (RAD-seq), which can be used to identify genome-wide single-nucleotide polymorphism (SNPs), to reveal detailed within-species genetic variations. Using the variable SNP loci identified from this analysis, we successfully evaluated the population-level genetic diversity and patterns of gene flow among multiple populations of C. japonicum around Japan. The results of genetic analysis basically showed that gene flow is widely maintained in the geographic range examined in this study, but the analysis in combination with larval dispersal simulations revealed several populations that were genetically distinct from the other populations, suggesting geographically limited gene flows. The information obtained from this study will be useful for the design of effective management schemes for C. japonicum, which is under threat from overfishing.